Cross-Border Personal Data Transfers after the Indonesia-United States Agreement on Reciprocal Trade (ART) - Dodik Setiawan Nur Heriyanto (Universitas Muhammadiyah Surakarta, 2026)
The commitment of the Agreement on Reciprocal Trade (ART) between Indonesia and the United States is a big step forward in how cross-border personal data transfers are handled. In this context, Indonesia has affirmed its dedication to ensuring legal certainty for the transfer of personal data to the United States. This agreement positions Indonesia as unequal, where data under its control can be transferred to the United States without any barriers. This article analyzes the legal ramifications of such commitment through the lens of international treaty law, specifically regarding the necessity of parliamentary approval. Article 10 of Law No. 7 of 2014 on Trade regulated that international trade agreements that have an enormous impact on society, cost the state budget, or require changes to current laws must be approved by law. Because cross-border transfers of personal data could violate basic privacy rights and conflict with Indonesia's data protection laws, the question is whether ART needs the House of Representatives' approval. The Constitutional Court Decision No. 137/PUU-XXIII/2025, on the other hand, offers a different interpretation. It mentions that international agreements about cross-border personal data transfers do not always need to be approved by law. This article critically examines the conflict between statutory mandates and constitutional interpretation, evaluating its consequences for democratic accountability and the safeguarding of individual rights. Furthermore, Indonesian trade law requires legislative approval for any ratification of a trade agreement that has consequences to the domestic economy. The study also contends that transparency in treaty-making processes is crucial for maintaining legal certainty, adherence to constitutional mandates, and the robust safeguarding of personal data in international trade relations.